Modeling and Analyzing the Spread of Flash Disk Worms via Multiple Subnets - Guihua Li; Zhenzhen Peng; Lipeng Song (Discrete Dynamics in Nature and Society)
The Flash Disk worms, spreading via both Web-based scanning and removable devices between multiple subnets, have become a serious threat to the Internet, especially those physically isolated subnets. We present a model which incorporates specific features of these worms in this paper. Then, we analyze the dynamic behaviors of the model when one subnet is considered. Analytical result shows that the Flash Disk worm can self-perpetuate when Ri0>1 and will die out otherwise. When multiple subnets are considered, we get that once a computer is infected by the Flash Disk worms, other computers in that subnet will be infected in a short time. Thus, for any subnet, to contain the Flash Disk worms, the most effective way is to prevent the first infected individual by improving the users’ security awareness of using removed devices. Our results are illustrated by numerical simulation.